Performance of RaCe Instrumentation System in Curved Root Canals: A Comprehensive Analysis by Three Study Methods - Leonardi,Denise Piotto (2013)
In this study, curved maxillary molar root canals were instrumented with RaCe rotary system to evaluate: 1. the occurrence of canal transportation using a radiographic platform; 2. the action of the instruments on the dentin walls, centering ability and canal enlargement by analysis of digital images; and the percentage of regular dentin surfaces and debris within the canal by histological analysis. Ten mesiobuccal roots of extracted human maxillary molars were embedded in acrylic resin and sectioned at the middle and apical thirds. Root canal shaping was performed using the RaCe rotary system at 250 rpm and 1 Ncm torque. Each instrument set was used five times according to a crown-down technique in the following sequence: 40/0.10, 35/0.08, 25/0.06, 25/0.04, 25/0.02 (working length - WL), 30/0.02 (WL) and 35/0.02 (WL). Each instrument was inserted until resistance was felt and then pulled back, followed by brushing movements towards all canal walls. Each specimen was assessed by three study methods: radiographic platform, digitized image assessment and histological analysis. The radiographic platform showed lack of apical transportation. No statistically significant difference (Wilcoxon test, p>0.05) was found between the middle and apical thirds regarding instrument action on dentin walls, centering ability, area of root canal enlargement, percentage of regular dentin surfaces and debris within the root canal. It may be concluded that RaCe system is a suitable method for the preparation of curved root canals, regarding the maintenance of root canal original path, action on dentin walls, canal enlargement and removal of debris from the root canal lumen.